Clinical significance of platelet reactivity during prasugrel therapy in patients with acute myocardial infarction. Issue 1 (July 2017) - Sato, Tetsuya; Namba, Yusuke; Kashihara, Yuya; Tanaka, Masamichi; Fuke, Soichiro; Yumoto, Akihisa; Saito, Hironori
Abstract: Background: Although some studies have examined platelet reactivity (PR) during prasugrel treatment, little is known about PR during the early treatment period and its clinical significance in Japan. Methods: We investigated the early and medium-term efficacy and safety of prasugrel in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI). Seventy-eight patients were enrolled and PR was measured (in P2Y12 reaction units; PRU) by the VerifyNow P2Y12 assay (Accumetrics, San Diego, CA, USA). Results: In 44 patients, serial measurement revealed that PR was significantly higher at 2 h after administration of the 20-mg loading dose of prasugrel than on the morning of the second day at 17.6 ± 6.6 h after administration (191.6 ± 75.5 vs. 138.5 ± 68.9 PRU). During the 8-month follow-up period, bleeding events occurred in 18 patients (23.1%) (GUSTO minor: 15 patients). Multivariate regression analysis identified oral anticoagulant use as a significant predictor of bleeding events during admission [odds ratio (OR): 4.214, 95% confidence interval (CI): 1.005–17.669, p  = 0.049]. Administration of prasugrel via a nasogastric tube was a significant predictor of high on-treatment platelet reactivity (HTPR) (PRU ≥ 230) (OR: 43.100, 95% CI: 4.517–411.251, p  = 0.001). In addition, HTPR was a significant predictor of major adverse cardiac events (cardiovascular death, non-fatal myocardial infarction, stent thrombosis, stroke, and sustained ventricular tachycardia) during the 8-month follow-up period (OR: 4.911, 95% CI: 1.164–20.722, p  = 0.030). Conclusions: It is feasible to treat AMI patients with prasugrel. HTPR is a significant independent risk factor for adverse events in AMI patients receiving prasugrel after primary PCI.